Persistent injury-associated anemia and aging: novel insights - Loftus, Tyler J. (J Trauma Acute Care Surg, 2018)
BACKGROUND: Hypercatecholaminemia and bone marrow dysfunction have been implicated in the pathophysiology of persistent-injury associated anemia. The elderly may be more vulnerable to bone marrow dysfunction due to high basal and peak catecholamine levels and impaired hematopoietic progenitor growth. We hypothesized that aging would adversely affect persistent injury-associated anemia. METHODS: Male Sprague Dawley rats age 8-9 weeks and F344-BN rats age 25 months were randomized to: naïve controls, lung contusion plus hemorrhagic shock (LCHS), and LCHS plus daily chronic restraint stress (LCHS/CS). Urine norepinephrine was measured on days one and seven. Mobilization of hematopoietic progenitor cells (HPC), bone marrow colony forming units-erythroid (CFU-E) growth, and peripheral blood hemoglobin, mean corpuscular volume (MCV), and red cell distribution width (RDW) were assessed on day seven. **p <0.05 young vs. aged counterpart by one-way analysis of variance. RESULTS: Aged rats had higher norepinephrine levels at naïve baseline (97** vs. 27 ng/mL) and seven days following LCHS/CS when compared to young (359** vs. 127 ng/mL). Following LCHS/CS, HPC mobilization was greater among young rats when compared to aged (5.4 vs. 2.5%). CFU-E growth was lower among aged animals for each group (naïve: 47** vs. 65; LCHS: 40** vs. 50; LCHS/CS: 38** vs. 44 cells/plate). Aged naïve rats had higher initial hemoglobin (15.2** vs. 14.3 g/dL), but lower MCV (48** vs. 59 fL/cell) and larger RDW at baseline, and greater differences seven days after LCHS/CS (MCV: 46** vs. 60 fL/cell; RDW: 17.4** vs. 16.3%). CONCLUSIONS: Compared to young rats, aged rats had less HPC mobilization despite elevated basal and peak norepinephrine. Aged rats were disproportionately affected by impaired hematopoietic progenitor growth and an iron-restricted red blood cell phenotype at baseline which persisted seven days after injury. Further research is needed to assess how the clinical approach to persistent-injury-associated anemia should differ for elderly trauma patients. LEVEL OF EVIDENCE: Prognostic study, level III